Dawr al-maktabāt al-raqamiyyah fī da‘m wa-nashr buḥūth al-lughah al-‘Arabiyyah wa al-Islāmiyyah fī Nigeria - Ibrahim Abdulmumin, Abdulmumin; Abubakr, Sunusi Sulaiman (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This study aims to explore the concept and significance of scientific research, particularly the types of scientific studies available in Arabic and Islamic studies in Nigeria. It also examines the definition and role of digital libraries, highlighting the key challenges they face and the difficulties encountered by researchers and students in accessing Arabic scholarly content. The research employs a descriptive-analytical method to investigate the role of digital libraries in supporting and disseminating Arabic and Islamic research in Nigeria. The significance of this study lies in its emphasis on promoting the role of digital libraries in advancing Arabic and Islamic scholarship, as well as encouraging researchers and intellectuals to engage more with this field. The study seeks to answer several core questions: What is the definition, significance, types, conditions, and objectives of scientific research? What types of Arabic-language research exist in Nigeria in the field of Islamic studies? What is the concept of digital libraries? What challenges do digital libraries face, and what obstacles hinder researchers and students from accessing Arabic academic resources? What is the role of digital libraries in supporting and disseminating Arabic and Islamic research in Nigeria? The findings reveal that digital libraries facilitate easier, faster, and more cost-effective access to books and research materials. However, challenges include limited researcher training in digital library usage, poor infrastructure, weak internet connectivity, and digital illiteracy among some scholars. Ultimately, digital libraries have played a significant role in supporting Arabic-language scientific production in Nigeria. The study recommends organizing training workshops for Nigerian scholars, graduate students, and researchers on how to effectively utilize digital libraries.